Common characteristics of synchrotron radiation and light leaking from a bent optical fiber. (July 2016) - Artru, X; Ray, C
Abstract: Light leaking from a bent optical fiber shares many properties with synchrotron radiation : in ray optics, both lights are emitted tangentially to a light cylinder ; in wave optics, the emission mechanism involves a tunnel effect . The angular distributions of these two radiations are studied in parallel and found to be similar. The same is done for the impact parameter distributions. The latter show interference fringes of the Airy function type. The far field escaped from the fiber is calculated with the Volume Current Method . An optical system observing the impact parameter profile is proposed.